APLIKASI MOBILE PENGELOLAAN KALORI HARIAN UNTUK PENDERITA OBESITAS - Linda Apriyanti; Mina Ismu Rahayu; Nazar Muhammad Suseno (LPPM STMIK BANDUNG, 2018)
Obesity is a symptom of disease that has become a health and nutrition problem of the world community, both in developed countries and in developing countries. Obesity is a condition where there is accumulation of excess fat in a person's body, ideal weight is determined by Body Mass Index calculations that already have standards from the World Health Organization (WHO). Obesity can also occur if the calories of food consumed by a person are not digested completely by the body so it is converted into fat. In this Final Project has been designed an application that is used as a guide to help weight loss from obese people, and calculate the ideal weight.Here users are given several menu choices, the calculation of BMI and BMR and the selection of food menu. The method used in the design of this application using the prototype method. Keywords: calories, ideal body, Obesity, recording, smartphone